2013
DOI: 10.2188/jea.je20120119
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole and Prognostic Factors in Amyotrophic Lateral Sclerosis Long-term and Short-term Survival: A Population-Based Study of 1149 Cases in Taiwan

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a rare disease in Taiwan; thus, estimation of ALS mortality is difficult. We evaluated factors associated with ALS survival in Taiwan.MethodsThe study enrolled 1149 Taiwanese with a primary diagnosis of ALS during 1999–2008. Follow-up information was available for all patients; mean (SD) duration of follow-up was 2.91 (2.62) years. Medical interventions, including noninvasive positive pressure ventilation (NIPPV), tracheotomy, gastrostomy, and riluzole, were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
61
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 26 publications
11
61
3
3
Order By: Relevance
“…We decided to take point 0 as time of diagnosis even this could mislead the comparison to other studies, setting our patients appearing to have worse status in less time. Nevertheless, there is no study with better outcome compared to our data at 1, 5 or 10 years of follow-up (Table 1) [14,15,22,73,80].…”
Section: Compared To Population-based Studiescontrasting
confidence: 72%
See 1 more Smart Citation
“…We decided to take point 0 as time of diagnosis even this could mislead the comparison to other studies, setting our patients appearing to have worse status in less time. Nevertheless, there is no study with better outcome compared to our data at 1, 5 or 10 years of follow-up (Table 1) [14,15,22,73,80].…”
Section: Compared To Population-based Studiescontrasting
confidence: 72%
“…The factors that are thought to contribute to a better survival are: limb-onset, youth, better motor function, better respiratory status, stable weight, longer interval between appearing of symptoms and diagnosis, inter alia [21]. The therapeutic interventions including Riluzole combined with other measurements including tracheotomy infer modestly on the survival [22]. The symptomatic interventions (percutaneous gastrostomy, mechanical ventilation, tracheostomy and comprehensive care) are the ones specially claimed to be responsible for prolonged survival rates [21,23,24], even they are not related to the disease process itself.…”
mentioning
confidence: 99%
“…Clinical studies showed that survival time is shorter in more impaired patients 4,15 . Many studies showed that patients with ALS treated with riluzole (50 mg/twice a day) survive longer 6,15,23 . Lee et al 6 showed that the mortality rate among patients receiving riluzole was reduced by almost 66%.…”
Section: A19msmentioning
confidence: 99%
“…Many studies showed that patients with ALS treated with riluzole (50 mg/twice a day) survive longer 6,15,23 . Lee et al 6 showed that the mortality rate among patients receiving riluzole was reduced by almost 66%. However, patients who started treatment with severe and generalized clinical impairment had less benefit from riluzole.…”
Section: A19msmentioning
confidence: 99%
See 1 more Smart Citation